Los juegos tradicionales como alternativa de enseñanza para el desarrollo integral de los niños y niñas de los cuartos y quintos grados de la escuela “Teniente Hugo Ortiz”, de la parroquia El Valle, cantón y provincia de Loja, año lectivo 2013-2014 - Flores Torres, Wilson Fernando (2015)
This investigative study purpose was to inform and propose the traditional games to promote the integral development of children of the fourth and fifth degrees of the school "Teniente Hugo Ortiz", the Valley parish, canton and Loja province, school year 2013-2014", front which arises the following objectives: general: analyze the traditional games in education for the integral development of children of the fourth and fifth" degrees of the school "Teniente Hugo Ortiz"; Specifics: identify the Ecuadorian traditional games are played by both children and girls of the fourth and fifth degrees of the school "Teniente Hugo Ortiz"; determine the level of knowledge of the traditional games in education for the integral development of children of the fourth and fifth degrees of the school "Teniente Hugo Ortiz"; design a manual of Ecuadorian traditional games for the integral development of of the boys and girls of the school "Teniente Hugo Ortiz". The methods used for the development of this research were: scientist, the descriptive; the analytic - synthetic and theoretician or deductive, which helped me to the Organization, processing and analysis of information: to reach data were handled the techniques of the survey, the same applied to the teachers and students of the institution; in the same way was observation tab to determine the reality of traditional games such as alternative education for the integral development of children in the fourth and fifth grades. to reach the results "Teniente Hugo Ortiz" of the parish was investigated to 8 teachers and 50 students at the school del valle, canton and Loja province. Reaching end of q teachers just apply traditional games for integral development, so I would recommend to the authorities of the institution... the promotion of the traditional games in all socio-cultural activities which consist in the school calendar year, with the assistance of teachers, boys girls, and parents, so that they facilitate the rescue of the traditional and cultural identity of the community.